Plasma-type Gelsolin is Decreased in Human Blood and Cerebrospinal Fluid following Subarachnoid Hemorrhage - Chou, Sherry H-Y. (2011)
BACKGROUND: Subarachnoid hemorrhage (SAH) pathophysiology involves neurovascular proteolysis and inflammation. How these two phenomena are related remains unclear. We hypothesize that matrix metalloproteinases (MMPs) mediate the depletion of anti-inflammatory plasma-type-gelsolin (pGSN). METHODS: We enrolled 42 consecutive SAH subjects and sampled CSF and blood on post-SAH days 2–3, 4–5, 6–7, and 10–14. Controls subjects were 20 consecutive non-SAH hydrocephalus patients with lumbar-drains. LISA, western blotting and zymography were used to quantify pGSN and MMP-9. RESULTS: In CSF, pGSN was lower in SAH compared with control subjects on post-SAH days 2–3 (p =0.0007), 4–5 (p=0.041), and 10–14 (p=0.007). In blood, pGSN decreased over time (p=0.001), and was lower in SAH compared to control subjects on post-SAH days 4–5 (p=0.037), 6–7 (p=0.006), and 10–14 (p=0.006). Western blots demonstrated that SAH CSF had novel bands at 52 and 46 kD, representing cleaved pGSN fragments. Gelatin zymography showed that CSF MMP-9 was elevated in SAH compared with controls. Higher CSF MMP-9 correlated with lower CSF pGSN on post-SAH day 7 (r= −0.38; p= 0.05). CONCLUSION: SAH is associated with decreased CSF and blood pGSN and elevated CSF MMP-9. Novel cleaved pGSN fragments are present in CSF of SAH subjects, consistent with pGSN cleavage by MMPs. Since pGSN is known to inhibit inflammatory mediators, these findings suggest that MMPs may reduce pGSN and exacerbate inflammation after SAH. Further studies are warranted to investigate the mechanisms underlying MMP-pGSN signaling in SAH.